Informal Caring and Labour Market Outcomes Within England and Wales - Stephen Drinkwater (WISERD, 2011)
This paper focuses on the links between informal care provision and labour marketactivity at the sub-national level within the UK. Within-country analysis of this issuehas been very limited to date despite the wide regional variations in informal careprovision that are often present. This issue is important in the context of policydecisions in Wales and the rest of the UK because of relatively high levels ofinformal caring in some areas, especially in the South Wales Valleys. In particular,given that these areas typically have low economic activity and employment rates,labour market differences can be exacerbated by the provision of informal caring bypeople of working age. Despite the wide variations in informal care provision, it isfound that labour market outcomes do not differ markedly by different carecategories across spatial areas within England and Wales. However, the analysisreveals that labour market outcomes for males as well as females are heavilyinfluenced for those who provide high levels of caring, especially in the South WalesValleys. For example, the largest impact of caring on the probability of not workingfor males and for part-time work for females is seen in this area.